Assessing Patient-Centred Care for Chronic Pain: Validation of a New Research Paradigm - Emilie Paul-Savoie; Patricia Bourgault; Emilie Gosselin; Stéphane Potvin; Sylvie Lafrenaye (Pain Research and Management)
BACKGROUND: Chronic pain is a complex phenomenon resulting from biological, psychological and social factors, and the use of patient-centred care (PCC) appears to be a promising avenue for its treatment. Various methods have been used for measuring PCC in nurses and physicians (caregivers); however, methodological problems have been raised following the observation of real clinical encounters or standardized patient simulations. The development of new strategies is required.